First report of the white stem borer, Scirpophaga innotata (Lep.: Crambidae: Schoenobiinae), from Iran - R. Azimi; T. Sobh Zahedi; J. Hajizadeh (نامه انجمن حشره‌شناسی ایران, 2014)
We collected moth specimens from rice fields in the vicinity of the city of Lahijan in Caspian province of Guilan between 2011 and 2012. The light traps in the rice fields of the village of Pahmadan (37Â°16'12" N, 50Â°03'00" E) captured a number of specimens of Scirpophaga innotata (Walker), commonly known as white stem borer. The white stem borer is a major pest of rice in the south and southeast of Asia and Australia. This species is recorded from Iran for the first time.